When simplifying matrix expressions, always take into account any given properties of the matrices. In this case, we used \( A^2 = A \) (which means \( A \) is idempotent) to simplify the expression. Also, when expanding expressions like \( (I - 2A)^3 \), be sure to apply the binomial theorem carefully and simplify terms step by step. Always check for matrix properties such as \( I^3 = I \) to help streamline the process.
\( A(I - 2A)^3 + 2A^3 \) (Since \( A^2 = A \))
⇒\( \Rightarrow A(I - 2A)^3 + 2A \)
⇒\( A[I^3 - 3I^2(2A) + 3I(2A)^2 - (2A)^3] + 2A \)
⇒\( A[I^3 - 6I^2A + 12IA^2 - 8A^3] + 2A \)
⇒\( A[I^3 - 6I^2A + 12IA^2 - 8A] + 2A \) we know that \(( I^3= I)\)
⇒\( A[I - 6IA + 12A - 8A] + 2A \)
⇒\( A[I - 14A + 12A] + 2A \)
⇒\( A[I - 2A] + 2A \)
⇒\( AI - 2A^2 + 2A \)
⇒\( A - 2A + 2A \)
⇒\( A \)
Given expression:
\( A(I - 2A)^3 + 2A^3 \) (Since \( A^2 = A \))
Step 1: Simplify the expression using \( A^2 = A \):
\[ \Rightarrow A(I - 2A)^3 + 2A \]Step 2: Expand \( (I - 2A)^3 \):
Use the binomial expansion to expand \( (I - 2A)^3 \): \[ (I - 2A)^3 = I^3 - 3I^2(2A) + 3I(2A)^2 - (2A)^3 \] Substitute the powers of \( I \) and simplify: \[ \Rightarrow A[I^3 - 6I^2A + 12IA^2 - 8A^3] + 2A \]Step 3: Apply known identities \( I^3 = I \) and \( A^2 = A \):
\[ \Rightarrow A[I - 6IA + 12IA^2 - 8A] + 2A \] Since \( A^2 = A \), we replace \( A^2 \) with \( A \): \[ \Rightarrow A[I - 6IA + 12A - 8A] + 2A \]Step 4: Simplify further:
\[ \Rightarrow A[I - 14A + 12A] + 2A \] Simplify the terms inside the brackets: \[ \Rightarrow A[I - 2A] + 2A \]Step 5: Final simplification:
\[ \Rightarrow AI - 2A^2 + 2A \] Since \( A^2 = A \), we replace \( A^2 \) with \( A \): \[ \Rightarrow A - 2A + 2A \] Simplifying the terms: \[ \Rightarrow A \]Conclusion: The simplified result is \( A \).
Let $A = \begin{bmatrix} \cos \theta & 0 & -\sin \theta \\ 0 & 1 & 0 \\ \sin \theta & 0 & \cos \theta \end{bmatrix}$. If for some $\theta \in (0, \pi)$, $A^2 = A^T$, then the sum of the diagonal elements of the matrix $(A + I)^3 + (A - I)^3 - 6A$ is equal to
Let $ A $ be a $ 3 \times 3 $ matrix such that $ | \text{adj} (\text{adj} A) | = 81.
$ If $ S = \left\{ n \in \mathbb{Z}: \left| \text{adj} (\text{adj} A) \right|^{\frac{(n - 1)^2}{2}} = |A|^{(3n^2 - 5n - 4)} \right\}, $ then the value of $ \sum_{n \in S} |A| (n^2 + n) $ is: